A Study on Constitutional Protection for Minorities in India - P. Saleem Akram, (The Bioscan, 2025)
Diverse India is home to many religious, linguistic, and cultural communities. The Constitution ensures equality, liberty, and protection from discrimination for minority groups via many sections. Religious and linguistic minorities are permitted to maintain their culture and create educational institutions in accordance with Articles 29 and 30. Articles 14, 15, 19, and 25–28 promote secularism by emphasising equality and religious liberty. In accordance with these constitutional mandates, the government has instituted many minority empowerment initiatives. Notwithstanding these safeguards, minority groups encounter socioeconomic marginalisation, discrimination, and communal discord. Significant judicial decisions have elucidated and reinforced these essential protections. This article examines significant instances and the involvement of the state and court in minority rights to evaluate these essential protections. It delineates areas for further legal and policy interventions to address constitutional protection deficiencies and minority group concerns in contemporary India.